Estimativas de pesos econômicos para um sistema de produção de ovinos da raça morada nova, no semi-árido brasileiro - Pereira, Igor Daniell Costa (2010)
The economic values for traits of a meet sheep production system were calculated using Morada Nova hair sheep, raised under the conditions of native pasture in the Brazilian semi-arid region, as model. These economic weights were estimated using the equation of profit, profit = revenue – costs, after increase by one unit and 1% for each trait, evaluated on the average of the others. Whereas 1% increase in the trait, the economic values for lambing percentage (LP), litter size (LS), lambs mortality (LM), yearling mortality (YM), ewes and rams mortality (AM), female slaughter weight (FSW), male slaughter weight (MSW), ewe adult weight (EAW), ram adult weight (RW), carcass yield (CY), number of lambings per year (NLY), age at first lambing (AFL) and number of anthelminthic doses used per year (AC) were 1,439, 1,439, -0,254, -0,110, -0,054, 0,487, 0,767, -0,172, 0,005, 1,523, 1,439, -0,258 and -0,025, respectively, expressed in Brazilian currency (R$) per ewe per year. The traits that showed greater economic importance were CY, NLY, LP and LS. The traits that showed lower economic values were: RW, AC and AM. The production system with Morada Nova sheep grazing native “caatinga” pasture in Brazilian Northeast, exclusively for meat production, is profitable when taking into account all costs of production, including that of family labour. Carcass yield was shown to be an important selection objective. As it is expressed when the animal is slaughtered, further studies need to be carried out with this population to aid in the choice of appropriate selection criteria for the improvement of this trait.